Hybrid HIPIMS+MFMS power supply for dual magnetron sputtering systems - Oskirko, V.O.; Zakharov, A.N.; Pavlov, A.P.; Solovyev, А.А.; Semenov, V.A.; Rabotkin, S.V. (Vacuum, 2020)
The paper presents a novel power supply device that provides a hybrid technique of dual magnetron sputtering. This power supply generates a sequence of bipolar pulses which provides both mid-frequency and high-power impulse magnetron sputtering. This allows using the advantages of both techniques, while numerous adjustable parameters considerably enhance the capabilities of the magnetron sputtering system. In the proposed power supply circuit, special attention is paid to the output pulse formers and the power switch control. The experimental results are obtained for superimposed mid-frequency and dual high-power impulse magnetron sputtering. During the aluminum film deposition, the deposition rate, the ion current density on the substrate and the ion-to-atom ratio are regulated by changing the power ratio between mid-frequency and high-power impulse magnetron sputtering. •A novel power supply is developed for hybrid dual magnetron sputtering.•Power supply combines mid-frequency and high-power impulse magnetron sputtering.•The proposed power supply provides a wide range of adjustable parameters.•Al targets are sputtered to demonstrate the capabilities of the novel power supply.•Ion-to-atom ratio is regulated in a wide range during hybrid magnetron sputtering.